Unexpected outcome following radiofrequency ablation of a malignant biliary stricture - Kruger, Andrew J.; Krishna, Somashekar G. (Turkish Journal of Gastroenterology, 2018)
Abstract We present a case of a 60-year-old woman with extrahepatic cholangiocarcinoma and recurrent malignant biliary strictures status post placement of two overlapping distal bile duct uncovered self-expandable metal stents (SEMSs) who presented with biliary obstruction due to tumor/tissue ingrowth. She subsequently underwent radiofrequency ablation (RFA) through SEMS to improve biliary stent patency. Post-RFA, thermal injury was observed in the periampullary mucosa. She later developed acute pancreatitis. This is the first case of RFA-induced acute pancreatitis with endoscopic evidence of thermal injury. It should be noted that RFA-induced acute pancreatitis is a potential adverse effect as RFA through SEMS is being used more widely. Cite this article as: Kruger AJ, Krishna SG. Unexpected outcome following radiofrequency ablation of a malignant biliary stricture. Turk J Gastroenterol 2018; 29: 230-2.